AKTIVITAS ANTIOKSIDAN, KARAKTERISTIK KIMIA, DAN ORGANOLEPTIK TEPUNG KECAMBAH KEDELAI (Glycine max) DENGAN BERBAGAI VARIASI PENGOLAHAN - Resa Meisara; - Nurhidajah (Universitas Muhammadiyah Semarang, 2012)
Sprouts Processing into sprouts flour are an alternative preservation. Heating can be done by boiling, steaming and roasting. The purpose of this study was to determine the effect of variations in the processing of antioxidant activity, the chemical characteristics (protein and vitamin C) and the organoleptic properties of the soybean sprouts flour. The kind of processing soybean sprouts are control, steaming, boiling, and roasting. The design used was completely randomized design. ANOVA statistical analysis and further tested by LSD, while the organoleptic using Friedman test and further tested by Wilcoxon test. Research result; Antioxidant activity on the processing of steaming 38.91 ppm, roasting 37.94 ppm and boiling 36.42 ppm; The percent of polyphenols at steaming 3.27%, roasting 3.25%, and boiling of 2.62%; vitamin C at steaming 0,16% control 0.18%, roasting of 0.1%; The highest protein content of 44.44% at steaming, boiling 44.25%, while the lowest protein 41.98% at roasting. It not significant effect of antioxidant activity, polyphenols, protein content, except for vitamin C. Analysis of Statistical at organoleptic properties was significant at aroma and color buat texture it was not significant. Keywords: Sprouts Soybean Flour, Antioxidant activity, polyphenol, protein, Vitamin C